Clinico-Epidemiological Profile and Outcome of Acute Poisoning Patients admitted to Intensive Care Unit in A Tertiary Level Private Hospital in Bangladesh - Rahman, A K M Ferdous; Nasif, Zubaer Wasit; Kafi, Saifullah Al; Sultana, Sabrina; Islam, Md Foyjul (Bangladesh Critical Care Journal, 2024)
Background: Acute poisoning is a prevalent health issue necessitating Intensive Care Unit (ICU) admission in developing countries. This study evaluates the socio-demographic characteristics, clinical parameters, and outcomes of acute poisoning patients admitted to the ICU in a tertiary level private hospital in Bangladesh. Method: This retrospective cohort study was conducted at tertiary care private hospital in Narayanganj, Bangladesh. Data was collected from ICU medical records from January 2023 to April 2024, enrolling a total of 57 patients aged 18 years or more who presented with acute poisoning. Data analysis was performed using Stata (Statistical Software for Data Science) 17.0(p < 0.05) Results: Out of 57 patients, 52.63% were females, with mean age of 27.84 years. Suicidal intent accounted for 84.21% of cases, and the primary reasons for poisoning included marital (61.40%) and familial disharmony (15.79%). The predominant type of poisoning was due to sedatives (17.54%) followed by aluminium phosphide (14.04%), and stupefying agents (14.04%). Aluminium phosphide poisoning had a 100% fatality rate, while sedatives and several other agents had 100% recovery rate. Statistical analysis showed a significant association between the type of poison and the final outcome (χ2(15) = 38.7996, p = 0.001). Conclusion: The study highlights the prevalence of intentional poisoning among young adults, especially females, with sedatives, aluminium phosphide, and stupefying agents being the most common. The high mortality rate from aluminium phosphide underscores the need for strict regulations and public awareness to control access to these substances. Bangladesh Crit Care J September 2024; 12 (2): 89-95